Constraining crustal thickness and lithospheric thermal state beneath the northeastern Tibetan Plateau and adjacent regions from gravity, aeromagnetic, and heat flow data. (1st June 2021) - Gao, Guoming; Lu, Quanming; Wang, Jun; Kang, Guofa
Graphical abstract: Highlights: Changed to: Friction due to subduction caused heat upwelling to the Qiangtang Block. A NE trend zone with high heat flow extends from the Bayan Har-Qilian Orogen to Alxa. The Qinling Orogen is a heat channel from Songpan-Ganzi Plateau to North China Plain. Abstract: The northeastern Tibetan Plateau (NETP) is located at the intersection between the Northern China Block, Southern China Block, and Tibetan Plateau, representing the frontier of the northeastward extrusion of the plateau. Data of gravimetry, aeromagnetic survey, and terrestrial heat flow are integrated to investigate the Moho depth, the Curie surface depth, and the thermal lithospheric thickness beneath the NETP and adjacent regions, which appear to be 30–70 km, 18–42 km, and 80–150 km, respectively. The gravity and the magnetic anomalies well reflect the spatial variation of tectonic structures. The NETP has a deep Moho but a shallow Curie surface. In contrast, the North China Plain, Ordos Basin and Yangtze Block have a reverse situation. The distributions of the Curie surface and heat flow both reveal that heat flow has north-eastwardly crossed the Qilian Mountain and has conducted into the Alxa Block. Moreover, the distribution of heat flow confirms that the Qinling Orogen behaviors as a heat channel (between Ordos Basin and Sichuan Basin) from Songpan-Ganzi Plateau to North China Plain. The eastward hot asthenosphere from the NETP may thin out the LAB beneath the North China Plain, as verified by the thinning thermal lithosphere there.